An Analytic Treatment of the Falkner-Skan Boundary Layer Equation - Molla, Mohammad Riazuddin (Dhaka University Journal of Science, 2013)
The existence and uniqueness of a positive solution of a singular nonlinear boundary value problem formulated from the Falkner-Skan boundary layer equation, are studied. The constructive method such as the method of upper and lower solutions is used to show the existence and uniqueness of a positive solution. Dhaka Univ. J. Sci. 61(1): 139-144, 2013 (January) DOI: http://dx.doi.org/10.3329/dujs.v61i1.15115